2017
DOI: 10.1093/mnras/stx1137
|View full text |Cite
|
Sign up to set email alerts
|

A common-envelope wind model for Type Ia supernovae – I. Binary evolution and birth rate

Abstract: The single-degenerate (SD) model is one of the principal models for the progenitors of type Ia supernovae (SNe Ia), but some of the predictions in the most widely studied version of the SD model, i.e. the optically thick wind (OTW) model, have not been confirmed by observations. Here, we propose a new version of the SD model in which a common envelope (CE) is assumed to form when the mass-transfer rate between a carbon-oxygen white dwarf (CO WD) and its companion exceeds a critical accretion rate. The WD may g… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
120
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(125 citation statements)
references
References 183 publications
(263 reference statements)
5
120
0
Order By: Relevance
“…Recently, Meng & Podsiadlowski (2017) developed a new version of the SD model, i.e. the commonenvelope wind (CEW) model which is completely different from the optically thick wind (OTW) model in physics (Hachisu et al 1996).…”
Section: Methodsmentioning
confidence: 99%
“…Recently, Meng & Podsiadlowski (2017) developed a new version of the SD model, i.e. the commonenvelope wind (CEW) model which is completely different from the optically thick wind (OTW) model in physics (Hachisu et al 1996).…”
Section: Methodsmentioning
confidence: 99%
“…In the CD scenario the CEE forms the single WD merger product of the core and the WD companion. In the CEE-wind channel of the SD scenario the CEE ensures the right conditions to bring the WD to explode (Meng, & Podsiadlowski 2017). These suggest that an important time of evolution is the time from the end of the CEE to the explosion itself, i.e., t CEED .…”
Section: Common Envelope To Explosion Delay (Ceed) Timementioning
confidence: 99%
“…If the explosion takes place after a long delay, it might leave behind a subdwarf B star or a WD. In the CEE-wind SD scenario that Meng, & Podsiadlowski (2017) suggested, the explosion might occur shortly after a CEE if the WD is a hybrid CONe WD (Meng, & Podsiadlowski 2018). In this scenario, that Meng, & Podsiadlowski (2018) predict to be ≈ 5 − 10% of all SNe Ia, the WD accretes hydrogenrich material from the envelope of a giant star while it spirals-in and ejects the envelope.…”
Section: Introductionmentioning
confidence: 99%
“…Meng & Podsiadlowski (2018) even suggested that these two peculiar subclasses of SNe Ia share the same origin, i.e. from the hybrid CONe WD + MS system, based on a new developed version of singedegenerate model [common-envelope wind (CEW) model, Meng & Podsiadlowski 2017]. However, the CaII IR3 absorption features in the spectra of these peculiar SNe Ia are quite different from the normal SNe Ia.…”
Section: De and Ie Scenariosmentioning
confidence: 99%
“…the more massive the companion, the more likely to form a dense CSM by a wind (e.g. the commonenvelope wind, Meng & Podsiadlowski 2017). In addition, the age of an SN Ia from the SD channel is also dominated by the companion mass, i.e.…”
mentioning
confidence: 99%